(untitled) (Stato, Chiese e pluralismo confessionale, 2023)
Islam and processes of radicalization: a criminological view ABSTRACT: The process of radicalization of the so-called ‘third wave of jihad’, composed of children of immigrants who grew up at the margins of Western cities, is analysed. Radical Islam has offered such young people an ideology capable of recomposing their fragmented life stories, by making them fighters and martyrs in the West (homegrown fighters) or in the Caliphate (foreign fighters). The paper describes the models of radicalization processes of European jihadists, sketching the biographies of those who have joined the ‘holy war’. The reasons for such a choice are interpreted in light of criminological subcultural theories that move from normative and cultural conflicts and anomic frustration. The jihadist subculture is understood as a collective solution to the problems of adaptation in an exclusionary society, to transform the stigma into a sign of distinction. SOMMARIO: 1. La radicalizzazione islamica come questione di sicurezza nazionale - 2. Definire la radicalizzazione tra ideologie estremiste e azioni violente - 3. Le fasi del processo di radicalizzazione in Europa - 4. La marginalità urbana e il jihad - 5. L’ideologia islamica radicale violenta come subcultura del riscatto.